Test-retest reliability of a psychological well-being scale in hospitalized older adults - Ottenbacher, Margaret E. (2007)
BACKGROUND AND AIMS: To examine the reliability of a 6-domain psychological well-being instrument in older patients admitted to an acute care hospital unit. METHODS: A prospective reliability study was conducted using a convenience sample of 40 hospitalized patients aged 65 or older. The main measure was a 6-domain psychological well-being instrument including self-acceptance, positive relations with others, autonomy, environmental mastery, purpose of life, and personal growth. RESULTS: The mean age was 76.3 years [standard deviation (SD)=6.1], 72.5% were white and 57.5% were men. The mean length of stay was 4.9 days (SD=3.1). Test-retest (admission and discharge) intraclass correlation (ICC) values for the six domains were self-acceptance (0.79), positive relations with others (0.72), autonomy (0.79), environmental mastery (0.66), purpose in life (0.79), and personal growth (0.78). CONCLUSIONS: The 6-domain psychological well-being instrument demonstrated good reliability among a sample of hospitalized older patients. This instrument may be useful in a clinical setting to predict outcomes related to patient health and recovery.